Condensation models for the water–steam interface and the volume of fluid method. (July 2017) - Szijártó, R.; Badillo, A.; Ničeno, B.; Prasser, H.-M.
Highlights: Three models were developed to model condensation at the water–steam interface. The models can capture the mass transfer at the interface, and are suitable for computational fluid dynamics and the volume of fluid method. The Phase field theory was applied to model condensation. The models were implemented in the FLUENT solver. A sensitivity study was done on an experimental facility with horizontal water–steam flow. Abstract: We assess the quantitative capabilities of three condensation models. These models are: (1) Numerical iteration technique; (2) heat flux balance equation; (3) phase field. The numerical iteration technique introduces a mass and energy transfer at the interface, if the temperature of the corresponding cell differs from the saturation value. The second approach solves the heat flux balance equation at the interface, hence, the resolution of the thermal boundary layer around the liquid-vapor interface is necessary to obtain an accurate value for the condensation rate. The third technique is based on a recently derived phase field model for boiling and condensation phenomena. The models were implemented in FLUENT and the interface was tracked explicitly with the volume of fluid (VOF) method. The models were tested on the LAOKOON facility, which measured direct contact condensation in a horizontal duct. The results showed that the phase field model fit best the experimental results.